Obviousness around the clock - Yves Breitmoser; Sebastian Schweighofer-Kodritsch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
Li (2017) supports his theoretical notion of obviousness of a dominant strategy with experimental evidence that bidding is closer to dominance in the dynamic ascending clock than the static second-price auction (private values). We replicate his experimental study and add three intermediate auction formats to decompose this behavioral improvement into cumulative effects of (1) seeing an ascending-price clock (after bid submission), (2) bidding dynamically on the clock and (3) getting drop-out information. Li's theory predicts dominance to become obvious through (2) dynamic bidding. We find no significant behavioral effect of (2). However, both (1) and (3) are highly significant.
Keywords: C91; D44; D82; 330; strategy proofness; experiments; private value auction